Analysis of Students' Ability to Understand Mathematics Concepts for Class VIII SMP/MTS - Linda Ardani Afriliziana; Kartini Kartini (IKIP Siliwangi, 2021)
The ability to understand mathematical concepts is important in learning mathematics. Students are often having difficulty in understanding mathematical concepts when the learning process takes place. The purpose of this study was to describe students’ ability to understand mathematical concepts on linear equation system of two variables without given any prior treatment. The linear equation system of two variables materials test was conducted in class VIII.1 of SMPN 7 Tanjungpinang on Thursday, 29 April 2021, to 34 students. The instrument used is a test instrument for the understanding ability of mathematical concepts. Based on the data analysis that has been done, the percentage ability to understand mathematical concepts in question number 1 with the indicator of restating a concept, is 79% with high criteria. In question number 2, the indicator that identifies examples and not examples of a concept shows as much as 89%, which is a very high criteria. In question number 3, the indicator presents the concept in the form of a mathematical representation, which is 68% with high criteria. In question number 4, the indicator applies the concept in an algorithmic manner, which is 86% with very high criteria. In question number 5 with indicators of applying algorithms concept in problem solving as much as 60%, is high criteria. According to these data, it can be concluded that the students' ability to understand mathematical concepts in solving systems of linear equations in two variables questions is categorized as high with the percentage of 76,4%.